New QTLs for Spot Blotch Disease Resistance in Wheat (Triticum aestivum L.) Using Genome-Wide Association Mapping - Tomar, Vipin; Singh, Daljit; Dhillon, Guriqbal Singh; Singh, Ravi Prakash; Poland, Jesse; Joshi, Arun Kumar; Singh, Pawan Kumar; Bhati, Pradeep Kumar; Kumar, Suneel; Rahman, Mokhlesur; Tiwari, Budhi Sagar; Kumar, Uttam (Frontiers in Genetics, 2021)
Spot blotch disease caused by Bipolaris sorokiniana is a major constraint for wheat production in tropics and subtropics. The introgression of spot blotch resistance alleles to the disease susceptible lines is critical to securing the wheat production in these regions. Although genome-wide association studies (GWAS) for spot blotch were attempted earlier, the present study focused on identifying new QTLs for spot blotch under natural disease pressure in diverse field conditions. A total of 139 advanced spring wheat lines were evaluated in three environments (three years and two locations) in India and Bangladesh. The GWAS using 14063 polymorphic Genotyping-by-Sequencing (GBS) markers identified eight QTLs associated with spot blotch disease resistance belonging to eight chromosomes across the wheat genome. Here, we report the identified marker-trait associations, along with the allele effects associated with the disease. The functional annotation of the significant markers identified NBS-LRR, MADS-box transcription factor, and 34 other plant-related protein families across multiple chromosomal regions. The results indicate four promising new QTLs on chromosomes 1A (497.2 Mb), 1D (89.84 Mb), 2B (421.92 Mb), and 6D (6.84 Mb) associated with several disease resistance protein families. These results provide insights into new genomic regions associated with spot blotch disease, and with additional validation, could be utilized in disease resistance breeding efforts in wheat development.